Can I Keep My Religious Identity and Be a Professional? Evaluating the Presence of Religious Literacy in Education, Nursing, and Social Work Professional Programs across Canada - Margaretta Patrick; W. Y. Alice Chan (MDPI AG, 2022)
In much of the world, education, nursing, and social work are human-centred professions that aim to engage with individuals holistically. Yet, how much of their training prepares them for this manifold reality? In this article, we provide an overview of three Canadian societal contexts, examine the literature on religious literacy in higher education and in the Canadian context, and study the professional programs of education, nursing, and social work offered in the top-ranked universities in the three largest English-speaking provinces in Canada. We describe the incorporation of the Calls to Action issued by the Truth and Reconciliation Commission of Canada and the limited evidence of religious literacy evident in the online information provided about the chosen programs and then argue that religious literacy is a necessary component of the university preparation programs for those entering these human-centred professions. Student requests for religious literacy workshops provided by the Centre for Civic Religious Literacy (CCRL), a non-religious and non-profit organization that works with partners in communities across Canada, demonstrate a demand for such education.